EARLY TREATMENT OF CLASS II DIVISION 1 MALOCCLUSION USING TWIN BLOCK APPLIANCES: A CASE REPORT - Renie Kumala Dewi; Seno Pradopo; Sindy Cornelia Nelwan (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Malocclusion is dentofacial growth deviation from its normal size and shape, thus causing abnormal occlusion. One of its etiology is heredity. Removable twin block, a functional appliance that can be used in interceptive orthodontic treatment, can be used to treat Class II malocclusion with large overjet in children during skeletal growth and development. Case: An 11-year-old boy came to pediatric dental specialist clinic with Class II division 1 Angle malocclusion (SNA 82°; SNB 74°; ANB 8°, CVM CS 4, overjet 14 mm, overbite 7 mm, and convex profile). Removable twin block for Class II malocclusion was chosen as the therapy. Case management: Removable twin block appliance with acrylic occlusal bite block was used on maxilla and mandible separately. An angle of 70° was made in the occlusal bite block, which was made based on the bite registration wax during centric occlusion. This device is used 24-hours a day. Monthly dental visit was done to reduce the maxillary and mandibular occlusal bite blocks. After 9 months, an overjet of 5 mm was obtained. Cephalometry calculations became SNA 82°; SNB 7 9 °; ANB 3 °. The patient was given further phase 2 treatment with fixed orthodontic appliance. Conclusion: With proper case selection and good patient cooperation, removable twin block appliance can correct skeletal malocclusion, improve facial profile, reduce overjet and overbite, and correct molar relations.